(untitled) (Jurnal Manajemen dan Organisasi, 2020)
Today the internet has made such a large contribution in which around 132,7 million peoples in Indonesia use the internet actively and makes Indonesia becomes a country with the largest consumers of virtual transaction in Southeast Asia. McDelivery Mobile Application is one of long distance fast food ordering applications which is able to compete with the similar applications and have to achieve customer retention target. The method used is non probability sampling with snowball sampling technique with 100 respondents which is analyzed by Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. As the result, only the dimensions of Novelty and Stimulation with T-statistics amounted to 2,612 and 3,903(> 1,96) which had a significant effect, because they met the requirements of the T-statistic value greater than the T-table (1,96 at the real level of 0,05).